(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was conducted to identify the correlation between some epidemiological and bacterial characteristics of burn patients and their complications for the period from October to March 2018 for patients who were visiting or staying at AL- Yarmook hospital. One hundred patients were randomly selected after being examined and diagnosed by a specialist. The pre-prepared questionnaire for the epidemiological features of each patients, which included sex, age, marital or economic status, location of residence and the nature of the work of the patients was filled. While the bacterial side included the collection of skin swabs from areas exposed to burns (skin) and to all patients under sterile conditions and under the supervisions of the doctor supervisor the treatment of infected cases. Samples were transferred to the laboratory to complete bacterial laboratory test. Samples were planted on the special and general culture, and bacterial growth was observed followed by final diagnosis of isolates. The results showed that the rate of infection was high in females compare males (63% to 37%) respectively. While the incidence of burns was high in patients aged (16-30) 52%. The rate of infections was also high in patients with poor families (54%) while those living in rural areas had high rates of infection (41%). The results of primary bacterial transplantation gave a high positive result (78%). The total isolates obtained from all initial transplant samples were 92% isolates and a percentage (117.9%), a high and satisfactory rate. Gram negative bacteria isolates showed a higher frequency than gram positive (73.9) and (26.06%) respectively. It was noted that Pseudomonas spp was very high (48.9%) compared with rest of the positive or negative bacteria isolates, where the frequency presence of Klebsiella spp, Staphylococcus spp , Streptococcus SPP (25%), (18.4%), (7.6%) respectively. The results of the present study include the importance of epidemiological aspects in the cases of burns, whether as factors that assist or are ready to be injured or accelerated in the healing of the infected cases, in addition to the importance of early bacterial diagnosis of infection to control the complications of secondary infection of bacteria in cases of burns and thus easy medical treatment